The association between HIV-related stigma and the pptake of HIV testing and ART among older adults in rural South Africa: findings from the HAALSI cohort study - Mahlalela, Nomsa; Manne-Goehler, Jennifer; Ohene-Kwofie, Daniel; Adams, Leslie B.; Montana, Livia; Kahn, Kathleen; Rohr, Julia K.; Bärnighausen, Till; Gómes-Olivé, F. Xavier (Aids and behavior, 2024)
HIV testing and antiretroviral therapy (ART) remain critical for curbing the spread of HIV/AIDS, but stigma can impede access to these services. Using data from the Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa (HAALSI), we used a multivariable logistic regression to examine the correlation between HIV-related stigma, HIV testing and ART uptake in older adults. We used four questions to measure stigma, with three assessing social stigma (reflecting social distancing preferences) and one assessing anticipated stigma (disclosure concern). We combined the three social stigma questions to generate a social stigma score ranging from 0 to 3, with higher scores indicating higher stigma. Anticipated stigma was prevalent 85% (95% CI 0.84-0.86), and social stigma was also frequent 25% (95% CI 0.24-0.27). Higher social stigma scores correlated with decreased HIV testing for all participants with social stigma. Compared to those with a score of 0, odds of testing decreased with higher stigma scores (OR = 0.66, 95% CI 0.53-0.81, p = 0.000) for a score of 1 and (OR = 0.56, 95% CI 0.38-0.83, p = 0.004) for a score of 3. ART uptake also decreased with higher social stigma scores among people living with HIV (PLWH), although it was significant for those with a score of 2 (OR = 0.41, 95% CI 0.19-0.87, p = 0.020). These findings emphasize that HIV-related stigma hampers testing and ART uptake among older adults in rural South Africa. Addressing stigma is crucial for improving testing rates, early diagnosis, and treatment initiation among the older population and achieving UNAIDS 95-95-95 targets.